Negotiating conflict and controversy in the early modern book world - Wilkinson, Alexander S.; Kemp, Graeme (Library of the written word, 2019)
Part 1. Control and Circumvention -- Circumventing Censorship: the Rise and Fall of Reformation Print Centres / Drew Thomas -- A Weapon for Freedom of Speech and Thought: Printing the Censurae of the Sorbonne, 1500-1550 / Martine Furno -- The Bible in Contention: Roman Prohibitions and Italian Biblical Texts for the Mass / Edoardo Barbieri -- Part 2. Negotiating Competitive Environments -- A Whole New World? Publishing in the Dutch Golden Age / Andrew Pettegree -- Fear and Loathing in Weesp: Personal and Political Networks in the Dutch Print World / Arthur der Weduwen -- Almanac Production and the Antwerp Printing Community, 1588-1621 / Cara Janssen -- Women and Conflict in the Iberian Book Trade, 1472-1700 / Alejandra Ulla Lorenzo and Alba de la Cruz Redondo -- Debating Print in English prefatory Dialogue / Rachel Stenner -- Part 3. Reporting Controversy -- Military Camps in Military Manuals / Klara Andresova -- Translating Treason: Printed Accounts of Conspiracies Against Henri IV in France and England / Sara Barker -- Sustaining a City under Siege: Paris versus Henri de Navarre (7 May 30 August 1590) / Alexander S. Wilkinson -- A Household Affair: Henri IV's Royal Printers, 1589-1595 / Marc Jaffre -- Pamphleteering and Honour in Early Modern France: the Wars of the Mother and Son, 1619-1620 / Edwin Andrew Goi -- Foreign News in Times of Domestic Crisis: the Truce Conflicts, the Thirty Years' War and the Rise of the Dutch Newspaper / Helmer Helmers -- Defending the Fatherland Against the Butcher Prince: the 'nationalisation' of the Legal Environment of Conflict / Robert von Friedeburg.